Randomised comparison of two skin preparation methods in foot and ankle surgery. Issue 3 (September 2016) - Chang, Alice; Hughes, Adrian; du Moulin, William; Mukerjee, Chinmoy; Molnar, Robert
Highlights: Equivalent preparation time within the bag immersion group. No significant formation of bacterial growth in either preparation technique groups. The immersion technique is as effective as the current standard painting procedures. Non-sterile bag is safe to use with a simple technique. Abstract: Background: Foot and ankle surgery has an increased incidence of post-operative surgical site infections. The aim of this study was to examine the efficacy and efficiency of an alternative method of surgical site preparation for foot and ankle surgery. Method: Fifty-one volunteers were recruited for this study which compared standard gauze painting using 2% chlorhexidine with 70% alcohol to immersion of the foot and ankle in a non-sterile bag filled with 60 mL of the same solution and rubbing all skin surfaces (bag immersion method). Each method was applied to different feet of each volunteer in a randomised order. Commercially available impression agar slides were used to measure bacteria colony-forming-unit (CFU) counts from four areas of each foot after allowing the preparation to dry. Outcomes included CFU count and preparation time. Result: There was no difference between the methods in terms of CFU count (0 total CFU vs. 1). Preparation time was significantly shorter for the bag immersion method (63.98 s vs. 67.98 s). Two-side 90% confidence intervals (2.03–6.00) for the difference in means of preparation time demonstrated equivalence using a margin of ±20%. Conclusions: The bag immersion method is a valid alternative, equivalent in preparation timing and the elimination of transient skin flora when using 2% Chlorhexidine with 70% alcohol.